Systematic Review: Cytotoxicity Test of Bioactive Compounds of Asteraceae Family Plant Extracts on HeLa Cell Line - Yanti, Windi Nofri; Hulrahma, Mifta; Aprilia, Kharisma Annisa; Roza, Amelia; Ilham, Kurniadi; Maliza, Rita (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
HeLa cancer cells are cervical cancer cells due to Human Papillomavirus (HPV 18) infection and thus have different properties from normal cervical cells. In recent decades, the number of plant species used in alternative medicine for cervical cancer-related purposes has increased. This systematic review aims to facilitate the review of the potential bioactive compounds of plant medicines and analyze how medicinal plants affect cancer cells. Scientific related questions, databases to be used, selection of keywords, inclusion and exclusion criteria, definition of results and conclusions of selected articles are all elements included in this research search strategy. Eight articles met the inclusion criteria and examined plant-derived compounds for their toxicity to HeLa cell lines. The bioactive compounds of this plant inhibit the growth of cancer cells.